Habitual offenders: a true tale of nuns, prostitutes, and murderers in seventeenth-century Italy - Monson, Craig (The University of Chicago Press, 2016)
Bologna. Airing dirty linen ; A tale of two sisters ; The soldier of misfortune and the tailor's son ; A grave mistake ; Pas devant les domestiques ; Novus homo ; Light at the top of the stairs -- Rome. Dragnet ; Cat and mouse games ; Home court advantage -- Bologna. "In this town they're all malicious liars!" ; "I don't know this Suor Laura Vittoria!" ; "Se sara fatto pamphilio / I Barberini Andrano in Esilio" ; "A few days in jail for love of me" ; Return to the scene of the crime ; A gentleman never tells ; Unfinished business